PONDOK PESANTREN DAN KONTRUKSI PEMIKIRAN PENDIDIKAN K.H. IMAM ZARKASYI - El-Yunusi, Muhammad Yusron Maulana (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
K.H. Imam Zarkasyi provides evidence of the success of Islamic boarding school education, namely; The results of his scientific and spiritual education are in the form of mental provisions that will be used as capital for life, and with strong spiritual and mental capital, obtained while studying at madrasas and Islamic boarding schools, it is proven that he has the courage to live and find his own way of life; as farmers, traders, businessmen, teachers, preachers, officials and others. The courage to live encourages him to like work, without waiting for job opportunities provided by others. On the spiritual and mental aspects, namely Faith and Piety are invaluable driving forces for fulfilling the aspirations of the nation, and it would be better if these mental capitals were accompanied by adequate skills. But keep in mind, that a person's ability and enjoyment of work does not lie in the skills he already has, but in the underlying mentality and being the driving force. History records that many heroes have fallen from madrasas and Islamic boarding schools, and those who are still alive do not expect rewards or service stars